Nicotine supplementation blocks oocyte maturation in Rattus norvegicus - Meitria Syahadatina Noor; H.M Bahkriansyah; Widjiati Widjiati; Budi Santoso (Universa Medicina, 2013)
BACKGROUNDIndonesia has the third largest tobacco consumption in the world after China and India. Nicotine as the main component of cigarette smoke has negative effects on the reproductive system, such as oocyte maturation, ovulation, and fertilization, and increasing the diploidy of oocytes. The goal of this researchwas to evaluate the effect of nicotine on oocyte maturation in Rattus norvegicus.METHODSThis was an experimental study with post test only control group design. The subjects were 40 rats selected homogenously and randomly. They were divided into a control group (receiving carboxy-methyl-cellulose sodium and 3 treatment groups (I-III) receiving nicotine subcutaneously for 7 days at dosages of 21 mg/ kgBW, 41 kg/kgBW and 84/kgBW, respectively. The observations comprised oocyte maturation stage, viz. germinal vesicle (GV), germinal vesicle breakdown (GVBD), metaphase I and metaphase II. Data were analyzed by one-way Anova with á=0.05, followed by Tukey’s HSD test.RESULTSOne-way Anova showed significant differences in oocyte  maturation in all groups. Tukey’s HSD test showed that for GV, the differing groups were control and I, control and II, I and III. For GVBD, the differing groups were control and I, I andII, I and III. For metaphase I, the differing groups were control with I, II, and III, I and II, I and III. For metaphase II, the differing groups were control versus I, II, and III, I and II, I and III.CONCLUSIONLow dose of nicotine is capable of affecting oocyte maturation in Rattus norvegicus.